2011
DOI: 10.1371/journal.pone.0028034
|View full text |Cite
|
Sign up to set email alerts
|

Re-Treatment Tuberculosis Cases Categorised as “Other”: Are They Properly Managed?

Abstract: BackgroundAlthough the World Health Organization (WHO) provides information on the number of TB patients categorised as “other”, there is limited information on treatment regimens or treatment outcomes for “other”. Such information is important, as inappropriate treatment can lead to patients remaining infectious and becoming a potential source of drug resistance. Therefore, using a cohort of TB patients from a large registration centre in Lilongwe, Malawi, our study determined the proportion of all TB re-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 8 publications
4
9
1
1
Order By: Relevance
“…A similar fi nding was observed in Malawi, 9 where 38% of smear-negative 'other' TB cases received the Category II regimen and 51% received Category I. This fi nding indicates a lack of knowledge of or adherence to national guidelines that could be addressed by training clinicians.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…A similar fi nding was observed in Malawi, 9 where 38% of smear-negative 'other' TB cases received the Category II regimen and 51% received Category I. This fi nding indicates a lack of knowledge of or adherence to national guidelines that could be addressed by training clinicians.…”
Section: Discussionsupporting
confidence: 64%
“…5 Studies from India and Africa have shown that retreatment, failure and return after LTFU cases have poor treatment outcomes, with success rates of 50-60%. [6][7][8][9] Patient characteristics such as male sex, alcoholism and illiteracy, and health system factors such as long distances to TB clinics, lack of anti-tuberculosis drugs, inadequate health education and poor management of drug side effects are risk factors for return after LTFU or retreatment default. [10][11][12][13][14][15] Some studies have identifi ed characteristics of retreatment cases that infl uence…”
Section: Discussionmentioning
confidence: 99%
“…Above data is different from other studies in showing a female predominance like Hannock, Henry et al 8 at Malawi which shows 60% females in their study.…”
Section: Agecontrasting
confidence: 93%
“…Relapse was higher among TB ⁄ ART (5.0%) than TB-only patients (3.2%) and TB ⁄ HIV patients (2.6%; P < 0.001). TB ⁄ ART patients had the highest proportion of 'other' patients (13%; P < 0.001), patients who are more likely to be mis-categorised re-treatment cases and HIV co-infected (Tweya et al 2011). EPTB was most common among TB ⁄ ART (26.9%) and less common among TB ⁄ HIV (20.7%) and TB-only (16.2%; P < 0.001).…”
Section: Adults ‡ 15 Yearsmentioning
confidence: 99%